Removal of boron from industrial wastewater using PVP/PVDF blend membrane and GO/PVP/PVDF hybrid membrane by pervaporation - Özekmekçi, Mehtap; Ünlü, Derya; Çopur, Mehmet (Springer, 2021)
Removal of boron from water is a significant issue worldwide. Boron levels in waters containing high concentrations should be kept under control. Boron removal from the industrial wastewater released from Eti Mine Boron plants was investigated by using blend and hybrid membranes in a laboratory-scale pervaporation system. Polyvinylpyrrolidone/Polyvinylidene fluoride blend membrane and Graphene oxide/Polyvinylpyrrolidone/Polyvinylidene fluoride hybrid membranes were synthesized for this process. The membranes were characterized by using scanning electron microscopy, Fourier transform infrared, X-ray diffraction and contact angle measurements. Separation performance was evaluated in terms of flux, removal ratio of boron, and boron concentration in permeate within the membrane. Membranes showed higher separation performance in industrial wastewater. The highest boron removal was obtained as 99.86% with a flux of 0.755 kg/m2h when the 8 wt% graphene oxide loaded hybrid membrane was used. This study indicates that the Polyvinylpyrrolidone and Graphene oxide addition improved the membrane features and separation performances of the pervaporation process with improved hydrophilic membrane features can be preferred as an innovative water treatment method for the removal of boron from industrial wastewater. The obtained results show that pervaporation can be readily adapted to the removal of boron species by appropriate membrane selection.
Keywords: Boron; Membrane; Pervaporation; Industrial Wastewater